2020
DOI: 10.3390/v12020154
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products-Derived Chemicals: Breaking Barriers to Novel Anti-HSV Drug Development

Abstract: Recently, the problem of viral infection, particularly the infection with herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2), has dramatically increased and caused a significant challenge to public health due to the rising problem of drug resistance. The antiherpetic drug resistance crisis has been attributed to the overuse of these medications, as well as the lack of new drug development by the pharmaceutical industry due to reduced economic inducements and challenging regulatory requirements. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 122 publications
1
55
0
4
Order By: Relevance
“…Notably, the comprehensive review article that has been published in the journal Viruses (Special Issue "Recent Advances in Herpesviruses Research: What's in the Pipeline?") by Treml et al [20] documented a large number of natural bioactive molecules and macromolecules with anti-herpes simplex virus properties along with their mechanisms of action. Although this paper has focused on the bioactivity against herpes simplex viruses, we cannot rule out that the reviewed natural products might have additional antiviral effects on various types of coronavirus, including SARS-CoV-2.…”
mentioning
confidence: 99%
“…Notably, the comprehensive review article that has been published in the journal Viruses (Special Issue "Recent Advances in Herpesviruses Research: What's in the Pipeline?") by Treml et al [20] documented a large number of natural bioactive molecules and macromolecules with anti-herpes simplex virus properties along with their mechanisms of action. Although this paper has focused on the bioactivity against herpes simplex viruses, we cannot rule out that the reviewed natural products might have additional antiviral effects on various types of coronavirus, including SARS-CoV-2.…”
mentioning
confidence: 99%
“…Therefore, the obtained results by this research could be rationalized with other studies in which various natural products have shown in various preclinical investigations the capability of inducing excellent anti-HSV activities with diverse mechanisms of action that could break barriers to novel anti-HSV drug development. This has been documented in a recent review article in which a large number of natural biomolecules extracted from various natural sources with outstanding activities against HSV infections were comprehensively reviewed [28].…”
Section: Assessment Of Cytotoxicity and Antiherpetic Propertiesmentioning
confidence: 97%
“…The main UPLC-Ms/Ms-identified molecules and their relative pharmacological activities are reported in Table 5. Antiviral [31,32] Antibacterial [33] Antifungal [34] Antioxidant [24] Antitumor [30] Myricetin Flavonoids Antibacterial [41] Antiviral [31,32,42] Antifungal [34] Antioxidant [24] Antitumor [30] Notes: * RT: retention time; n.r. : not reported.…”
Section: Antioxidant Activity and Total Phenolic And Flavonoid Contentsmentioning
confidence: 99%